A PILOT PLANT FOR THE BIOGAS PRODUCTION - A. Omrani; M. Ghiasseddin (Tehran University of Medical Sciences, 1988)
Manure and Putreseible garbage are some of the main sources of pathogenic germs in countryside's. On the other hand, demand for fertilizer and energy increases in rural areas every day. To study Potential of cow manure for these requirements a 16,5m3 pilot plant was designed and constructed as fermentation tank near animal husbandry of karaj Agriculture Faculty. Some 260kg cow manure and water with the ratio of 4 and 7 was fed to fermentation tank every day. Average daily biogas production was 3.4m3, which was burned successfully in a gas range. Gas production was reduced by 86% during coldest winter days. Design for control of gas pressure and reservation of excessive gas was successful. Concentration of nitrate in sludge increased by 1.6 folds compared to row material. Some bacteria and Parasites were reduced drastically.